Comparing the Net Benefit of Forestland Access for Big-Game Hunting across Landownership Types in Georgia, USA. Issue 2 (26th September 2018) - Mingie, James C; Poudyal, Neelam C; Bowker, J M; Mengak, Michael T; Siry, Jacek P
Abstract: Big-game hunting is a popular recreation activity on public and private land. No study in the forest economics literature has examined hunting demand by comparing price response and value across different land-ownership classes. By combining travel cost modeling with data collected from a mail survey of licensed big-game hunters, this study estimated and compared the economic value of hunting trips across land ownership types in Georgia, USA. Results indicated that hunting-trip demand was influenced by age, income, retirement status, experience, and the presence of food plots with price response differences across land access types. Hunters on public and nonleased private lands appeared more sensitive to price changes than hunters on leased and personally owned land. The net economic benefit of hunting access varied across access types, with hunting trips to leased and personally owned land yielding more than twice the benefit per trip as nonleased private land or public land. This difference generally increased as travel time costs were factored into the models. Findings will be useful in understanding the net economic benefit of big-game hunting, as well as preferences for and price response to access on hunting lands under different ownership regimes in the Southeast.